Effect of insulation location on the heat gain and losses for different climatic conditions - Ozel, M.; Pihtili, K. (Sila Science, 2012)
In this study, location of insulation to minimize heat gain and losses in the building walls is analysed for three different climatic locations of Turkey. In analysis, six various exterior wall configurations consisting of one, two and three layers of insulation are considered. Heat transmission loads in the multilayer wall structures are calculated by an implicit finite-difference procedure for a wall with south orientation. Calculations are made for July 15 and January 15 chosen to represent typical summer and winter conditions in Elazig, Kars and Izmir cities, Turkey. The results show that climatic conditions didn't change the most suitable location of insulation in the wall. For three different climatic, the smallest load fluctuation is obtained when each one of three equivalent insulation layers is placed on the outdoor surface, in middle and on the indoor surface of wall while the highest load fluctuation among all investigated wall configurations occurs when the insulation as one layer is placed on the indoor surface.
Keywords: Location of insulation; Heat gain and losses; Climatic conditions